2000
DOI: 10.1021/bi992786n
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the N-Linked Glycans on the 3D Structure of the Free α-Subunit of Human Chorionic Gonadotropin

Abstract: To gain insight into intramolecular carbohydrate-protein interactions at the molecular level, the solution structure of differently deglycosylated variants of the R-subunit of human chorionic gonadotropin have been studied by NMR spectroscopy. Significant differences in chemical shifts and NOE intensities were observed for amino acid residues close to the carbohydrate chain at Asn78 upon deglycosylation beyond Asn78-bound GlcNAc. As no straightforward strategy is available for the calculation of the NMR struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 26 publications
(45 reference statements)
3
38
0
Order By: Relevance
“…This, in turn, renders them amenable to high-resolution NMR studies, as exemplified by recent work on the glycosylated, 55 kDa Fc fragment of immunoglobulin G (Barb et al 2011). Thus, NMR constitutes the preferred tool for characterizing the structural and dynamic properties of sugar moieties in glyco-proteins (Fletcher et al 1994; Wyss et al 1995; Metzler et al 1997; Erbel et al 2000; Slynko et al 2009; Barb and Prestegard 2011). On the protein side, NMR has also been used to investigate the conformational properties of glycosylated-, and neighboring protein residues.…”
Section: Glycosylationmentioning
confidence: 99%
See 1 more Smart Citation
“…This, in turn, renders them amenable to high-resolution NMR studies, as exemplified by recent work on the glycosylated, 55 kDa Fc fragment of immunoglobulin G (Barb et al 2011). Thus, NMR constitutes the preferred tool for characterizing the structural and dynamic properties of sugar moieties in glyco-proteins (Fletcher et al 1994; Wyss et al 1995; Metzler et al 1997; Erbel et al 2000; Slynko et al 2009; Barb and Prestegard 2011). On the protein side, NMR has also been used to investigate the conformational properties of glycosylated-, and neighboring protein residues.…”
Section: Glycosylationmentioning
confidence: 99%
“…Once established, N-glycosylation itself is rather long lived, whereas individual glycan structures may experience dynamic compositional changes during a protein’s lifetime (Stanley et al 2009; Schwarz and Aebi 2011). With regard to glycosylation-induced changes in local protein backbone conformations, N-glycosylation has been reported to promote β -turn conformations (Meyer and Moller 2007), stabilize folded protein domains (Wyss et al 1995) and increase the degree of order in human chorionic gonadotropin (Erbel et al 2000). Immunoglobulin G N-glycans exhibit conformational exchange between two states, one giving rise to contacts between the glycan chain and the immunoglobulin, the other one preventing such contacts (Barb and Prestegard 2011; Barb et al 2012).…”
Section: Glycosylationmentioning
confidence: 99%
“…The PDB database contains several hGTH structures: hCGa (PDB entries 1E9J, 1HD4, 1DZ7 and 1HCV (Spinelli et al, 1996;Erbel et al, 1999;Erbel et al, 2000)), hCG (PDB entries 1QFW, 1HRP, 1HCN (Lapthorn et al, 1994;Wu et al, 1994;Tegoni et al, 1999)), hFSH (PDB 1FL7 (Fox et al, 2001)), hFSH bound to hFSHR-ECD (PDB 1XWD (Fan and Hendrickson, 2005)) and the TSH binding domain of hTSHR (PDB 3GO4 (Sanders et al, 2007)). To compare these available structures we structurally superimposed them using the Discovery Studio 2.5 superposition by sequence alignment protocol.…”
Section: Structures and Models Of Gths And Their Receptorsmentioning
confidence: 99%
“…It is known that the region ␣33-57 is largely involved in signal transduction and significantly altered by subunit dissociation. According to Erbel et al (47), comparison of X-ray structures of intact deglycosylated hCG and NMR structure of ␣-subunit in solution revealed that the dissociation of the hormone dimer induces large structural changes in the ␣-subunit, resulting in increased mobility of the glycan at Asn-52. Recently also, the structure of intact and deglycosylated hCG in complex with two Fv fragments of high-affinity anti-␣ and anti-␤ monoclonal antibodies has been solved.…”
Section: Carbohydrate Chainsmentioning
confidence: 99%